EFEKTIVITAS PENGGUNAAN AKUN INSTAGRAM @NGAWIKAB SEBAGAI MEDIA KOMUNIKASI DENGAN MASYARAKAT KABUPATEN NGAWI: Suatu penelitian tentang efektivitas akun instagram sebagai media komunikasi dengan masyarakat (Universitas Merdeka Madiun, 2025)
The research in this thesis aims to determine whether there is an effective use of the @ngawikab Instagram account as a medium of communication with the people of Ngawi Regency. The theory in this thesis research uses the Theory of Uses and Effects and Effectiveness. The theory that relates between users, media, audience and effects (Rohim, 2009). The measure of effectiveness is seen from the level of intensity and satisfaction as well asthe communication that occurs (Sudarwan Danim, 2004). The method used in thisthesis research is a quantitative method. By using a questionnaire in data collection. In this thesis research also uses the Cluster Random Sampling technique. Based on the research that has been done, the researchers draw the conclusion that it can be said that the Instagram account @ngawikab is quite effective as a medium of communication with the people of Ngawi Regency based on 100 questionnaires that have been distributed to respondents, but in reality the Instagram account @ngawikab can be said to be less effective in the interaction is still a lot of posts that have no comments in the comments column and the number of likes also tends to be small compared to the number of followers. The value of the regression direction coefficient is 0.896, which means that it has an influence on the effectiveness of using the Instagram account @ngawikab by 65.5%.